Prediction of Density and Molar Volume for Mixtures of Nitrogen with Neon, Argon and Methane Using the Statistical-Mechanically Equation of State¶ - HAGHIGHI, BEHZAD; MEHDI PAPARI, MOHAMMAD; GHASEMI, HAMID; NIAFARI, MARYAM (Asian Journal of Chemistry, 2010)
In this paper, the analytical equation of state (EoS) proposed by Ihm-Song-Mason (ISM) was applied to calculate molar volume and density of mixtures of nitrogen with neon, argon and methane. The pair interaction potential has been used to evaluate the second virial coefficients and the ISM EoS parameters (i.e. α and b). The calculated values of aforesaid quantities were applied to predict the molar volumes for mixtures of nitrogen with neon, argon and methane. Agreement with experiment was excellent for all the systems.